-2(4+m)+6(m-3)=14

Simple and best practice solution for -2(4+m)+6(m-3)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4+m)+6(m-3)=14 equation:


Simplifying
-2(4 + m) + 6(m + -3) = 14
(4 * -2 + m * -2) + 6(m + -3) = 14
(-8 + -2m) + 6(m + -3) = 14

Reorder the terms:
-8 + -2m + 6(-3 + m) = 14
-8 + -2m + (-3 * 6 + m * 6) = 14
-8 + -2m + (-18 + 6m) = 14

Reorder the terms:
-8 + -18 + -2m + 6m = 14

Combine like terms: -8 + -18 = -26
-26 + -2m + 6m = 14

Combine like terms: -2m + 6m = 4m
-26 + 4m = 14

Solving
-26 + 4m = 14

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + 4m = 14 + 26

Combine like terms: -26 + 26 = 0
0 + 4m = 14 + 26
4m = 14 + 26

Combine like terms: 14 + 26 = 40
4m = 40

Divide each side by '4'.
m = 10

Simplifying
m = 10

See similar equations:

| 4(5x-4)+10=-3 | | 20+8(11-q)=-12 | | 240=126-v | | 6x-12x+9=-27 | | -24-5x=-4(x+5) | | y=101.21x+0.0991 | | 2(3*-0.5+2)-2*-0.5=6*-0.5+5 | | 3(4j-3)8=-1+12j | | 12a+99a=3885 | | -11u-6=3u^2 | | 32-8p=-8(4p+2) | | 7+x=8x-2 | | -7-3v-10+3v=0 | | 5x+48=3x-36 | | 2(3*0.5+2)-2*0.5=6*0.5+5 | | 11x^2y^2=33x^2y | | 3(6s+12-10s-6)=0 | | 3(3n+4)=54+6x | | -5.2+9=-8 | | 22r+10-2= | | (x+7).3=33 | | 15-5x=-40 | | -5.8+9=-8 | | 2(3x+2)-2x=6x+5 | | X-45+45=540 | | .01x+.04y=-10 | | 5*x=-20 | | -6n+8=8-6n | | (3n-2)(4+n+1)=0 | | 20(2x-3)=(4x)5 | | -3*x=-29 | | -4x-5+2x=-14+3 |

Equations solver categories